First-principles study on the mechanical and electronic properties of energetic molecular perovskites AM(ClO4)3 (A = C6H14N22+, C4H12N22+, C6H14N2O2+; M = Na+, K+). Issue 38 (31st August 2022) - Li, Qiaoli; Li, Shenshen; Xiao, Jijun
Abstract : Using the pCOHP method it was revealed the band gap, and the modulus properties are related to the type and strength of the M–O bonds in a series of molecular perovskite high-energetic compounds AM(ClO4 )3 (A = C6 H14 N22 +, C4 H12 N22 +, C6 H14 N2 O2 + ; M = Na +, K + ). Abstract : Density functional theory (DFT) simulations were conducted to study the crystal structures, and mechanical and electronic properties of a series of new energetic molecular perovskites, including (C6 H14 N2 )[Na(ClO4 )3 ], (C6 H14 N2 )[K(ClO4 )3 ], (C4 H12 N2 )[Na(ClO4 )3 ] and (C6 H14 N2 O)[K(ClO4 )3 ], abbreviated as DAP-1, DAP-2, PAP-1, and DAP-O2, respectively. By calculating the elastic constants, moduli (Young's modulus E, bulk modulus B, and shear modulus G ), Poisson ratio ν and Pugh's ratio B / G, we found that the four energetic molecular perovskites not only possessed good mechanical stability but excellent mechanical flexibility and ductility. In addition, DFT calculations were used to investigate the electronic properties of all of the perovskite compounds. The band gaps of DAP-1 and DAP-2 were comparable, and the band gap of PAP-1 was the smallest and that of DAP-O2 was the largest. A comprehensive analysis of the density of states and the M–O bonding characteristics provided a good explanation for the band gap characteristics. Besides, we found that the modulus properties of these molecular perovskite energetic compounds are also tightly bound to the strength of M–O bonding.